2019
DOI: 10.1590/0074-02760190150
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological characterisation of Zika virus isolates from different Brazilian regions

Abstract: BACKGROUND Zika virus (ZIKV) infections reported in recent epidemics have been linked to clinical complications that had never been associated with ZIKV before. Adaptive mutations could have contributed to the successful emergence of ZIKV as a global health threat to a nonimmune population. However, the causal relationships between the ZIKV genetic determinants, the pathogenesis and the rapid spread in Latin America and in the Caribbean remain widely unknown. OBJECTIVES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
(29 reference statements)
0
19
1
1
Order By: Relevance
“…Notably, ZIKV MR766 is a laboratory-adapted strain, while the Asian isolates used in this study were recently obtained from Brazilian clinical samples not extensively passaged. 15 Remarkably, differences in the ability to downregulate IGF2 between the two recently obtained low-passage clinical Asian ZIKV isolates (ZV BR 2015/15261 and ZV BR 2016/16288) were observed. This finding was intriguing since similar RNA and percentages of cells expressing E protein were observed for both isolates ( Fig.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Notably, ZIKV MR766 is a laboratory-adapted strain, while the Asian isolates used in this study were recently obtained from Brazilian clinical samples not extensively passaged. 15 Remarkably, differences in the ability to downregulate IGF2 between the two recently obtained low-passage clinical Asian ZIKV isolates (ZV BR 2015/15261 and ZV BR 2016/16288) were observed. This finding was intriguing since similar RNA and percentages of cells expressing E protein were observed for both isolates ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…36 The mechanisms involved in the regulation of IGF2 gene expression by ZIKV need to be further investigated, but our results indicate the possible involvement of six amino acid differences found between the recent ZIKV clinical isolates ZV BR 2016/16288 and ZV BR 2015/15261 that map to NS1, NS2A, NS3 and NS4B proteins. 15 IGF2 expression modulation has been described for other viruses. Dysregulation of the IGF system by human papillomavirus (HPV), hepatitis B virus (HBV) and hepatitis C virus (HCV) is associated with disease progression and cancer development.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…ZIKV strains from Brazil and Uganda showed delayed activation of the innate immune responses mediated by RIG-I as compared to the milder Cambodia strain that correlates with their pathological outcomes ( Esser-Nobis et al, 2019 ). Studies using these different strains in lung A549 cells revealed the important role of RIG-I sensing in early innate immune response and induction of Type I Interferon responses ( Strottmann et al, 2019 ). However, the role of this pathway in the host tropism of different isolates of ZIKV is yet to be fully uncovered that may provide a deeper insight into the importance of early viral sensing and productive IFN-response via the MAVS signalosome in ZIKV clearance.…”
Section: Insight Into Regulation Of Mavs Signalosome By Rna Virusesmentioning
confidence: 99%